(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This research was on the cybersecurity challenges and needs of grassroot users of cyberspace in Zimbabwe. A qualitative research methodology was used and was guided by the Interpretivist philosophy. Judgmental sampling was used to select the participants in the study based on their knowledge on cybersecurity matters. The sample was drawn from people from Murewa District of Zimbabwe. A descriptive research design was used to answer the research questions. Both unstructured and structured interviews as well as observations were used to collect data on the cybersecurity needs and challenges of grassroot users of cyberspace. The findings revealed that the challenges that grassroot users are facing include identity theft, poor internet connectivity and infrastructure problems. The research also exposed the need for stronger physical security of ICT assets and cybersecurity legislation. The researcher recommended the use of solar systems as an alternative source of energy and continuous review and alignment of cybersecurity legislation in line with the changing cyber threat landscape.